EFFECT GUIDED NOTE TAKING STRATEGY ON STUDENTS’ LEARNING MOTIVATION AT MTs NEGERI - Diah Wulan Safitri; Kholilur Rahman (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to examine the effect of the Guided Note Taking strategy on the learning motivation of eighth-grade students in the Qur'an Hadith subject at MTsN 5 Banyuwangi. This research employs a quantitative approach using a quasiexperimental design in the form of a pretest-posttest non-equivalent control groupdesign. The population in this study consists of all 8-grade students, totaling 120 individuals. A sample of 44 students was selected using cluster sampling. The study was conducted from November to March 2025. Data collection techniques included observation, interviews, questionnaires, and documentation. Data analysis techniques involved the Wilcoxon test and the independent sample t-test. The results indicate that the Guided Note Taking strategy significantly affects students' learning motivation. Based on SPSS version 25 using the Wilcoxon test, the significance value obtained was 0.000 < 0.05, thus Ha is accepted. This indicates that there is a significant influence of the Guided Note Taking strategy on the learning motivation of eighth-grade students in the Qur'an Hadith subject. The results of the independent sample t-test showed a tvalue of 8.282 > t-table value of 2.018, with a significance value of 0.000 < 0.05, leading to the acceptance of Ha. Therefore, there is a significant difference in learning motivation between students taught using the Guided Note Taking strategy and those taught using conventional methods.